Characteristics of Cancer Patients Presenting to an Integrative Medicine Practice-Based Research Network. (September 2014) - Edman, Joel S.; Roberts, Rhonda S.; Dusek, Jeffery A.; Dolor, Rowena; Wolever, Ruth Q.; Abrams, Donald I.
Objective: To assess psychosocial characteristics, symptoms and reasons for seeking integrative medicine (IM) care in cancer patients presenting to IM clinical practices.Study Design and Methods: A survey of 3940 patients was conducted at 8 IM sites. Patient reported outcome measures were collected and clinicians provided health status data. This analysis compares 353 participants self-identified as cancer patients with the larger noncancer cohort.Results: Mean age of the cancer cohort was 55.0 years. Participants were predominantly white (85.9%), female (76.4%), and well educated (80.5% completed college). For 15.2% of cancer patients, depression scores were consistent with depressive symptoms, and average scores for perceived stress were higher than normal, but neither were significantly different from noncancer patients. The most prevalent comorbid symptoms were chronic pain (39.8%), fatigue (33.5%), and insomnia (23.3%). In the cancer cohort, perceived stress was significantly associated with depression, fatigue, insomnia, pain, and QOL. Cancer patients who chose an IM clinical practice "seeking healthcare settings that address spirituality as an aspect of care" had significantly higher levels of perceived stress, depression, and pain than those not selecting this reason.Conclusions: Demographic characteristics, depression scores, perceived stress scores, and reasons for seeking integrative cancer care were not significantly different between cancer patients and noncancer patients. Perceived stress may be an important indicator of QOL. The association of perceived stress, depression and pain with seeking spirituality suggests that providing IM interventions, such as effective stress management techniques and pastoral or spiritual counseling, may be helpful to patients living with cancer.